2006
DOI: 10.1128/jvi.02299-05
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Kaposi's Sarcoma-Associated Herpesvirus Infection and Replication by MEK/ERK, JNK, and p38 Multiple Mitogen-Activated Protein Kinase Pathways during Primary Infection

Abstract: Infection by viruses alters signaling pathways as a result of cellular response to the infection and virus modulation of its environments. Viruses have evolved to depend on these altered cellular pathways for their successful infection and replication in the host cells. For example, modulation of mitogenactivated protein kinase (MAPK) pathways is essential for infection and replication of human immunodeficiency virus, hepatitis B virus, Epstein-Barr virus, and vaccinia virus (11,23,31,54), while modulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
147
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(156 citation statements)
references
References 57 publications
9
147
0
Order By: Relevance
“…Disruption of EBV latency by BRLF1 is prevented by inhibitors of p38 or JNK (Adamson et al, 2000). Another human herpesvirus, Kaposi's sarcoma-associated herpesvirus (HHV-8), has been reported to activate the ERK, p38 and JNK MAP kinase pathways during primary infection (Naranatt et al, 2003;Xie et al, 2005), and the activation of these pathways is essential for HHV-8 infection (Pan et al, 2006). Inhibitors of all three MAP kinase pathways reduce HHV-8 infectivity by reducing lytic replication and, as a result, the yield of infectious virions (Pan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of EBV latency by BRLF1 is prevented by inhibitors of p38 or JNK (Adamson et al, 2000). Another human herpesvirus, Kaposi's sarcoma-associated herpesvirus (HHV-8), has been reported to activate the ERK, p38 and JNK MAP kinase pathways during primary infection (Naranatt et al, 2003;Xie et al, 2005), and the activation of these pathways is essential for HHV-8 infection (Pan et al, 2006). Inhibitors of all three MAP kinase pathways reduce HHV-8 infectivity by reducing lytic replication and, as a result, the yield of infectious virions (Pan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another human herpesvirus, Kaposi's sarcoma-associated herpesvirus (HHV-8), has been reported to activate the ERK, p38 and JNK MAP kinase pathways during primary infection (Naranatt et al, 2003;Xie et al, 2005), and the activation of these pathways is essential for HHV-8 infection (Pan et al, 2006). Inhibitors of all three MAP kinase pathways reduce HHV-8 infectivity by reducing lytic replication and, as a result, the yield of infectious virions (Pan et al, 2006). HHV-6B may also exploit the cellular MAP kinase pathways during infection, as the presence of an inhibitor of p38 reduced the level of the 116 kDa viral nuclear protein significantly, as detected by Western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an increasing body of literature showing that JNK activation follows bacterial, fungal, prion, parasitic, or viral infections. Under these circumstances, JNK activation may influence important cellular consequences, such as alterations in gene expression (1,53,59,162,167,176,199,294,325,326,346), cell death (58,89,137,139,169,193,243,293), viral replication, persistent infection or progeny release (215,224,251,260), or altered cellular proliferation (178). The exact mechanism of JNK activation under each of these circumstances remains to be elucidated fully, although there may be involvement of Toll-like receptors, direct pathway modulation through interaction with upstream protein regulators, or the activation following an ER stress response (79,87,110,124,143,191,253,261,279,294,312).…”
Section: Fig 1 Overview Of the Jnk Pathway (A)mentioning
confidence: 99%
“…Kaposi sarcoma-associated herpesvirus (KSHV) is the etiological agent of endothelial neoplasm Kaposi sarcoma and two lymphoproliferative diseases, primary effusion lymphoma and multicentric Castleman disease. KSHV activates both MEK/ERK/RSK and AKT/mTOR/ S6K signaling pathways by multiple mechanisms (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). We recently found that the immediate early and tegument protein open reading frame 45 (ORF45) of KSHV interacts with RSK1 and RSK2 and causes sustained activation of RSK and ERK during lytic replication (17).…”
mentioning
confidence: 99%